Comparison of the myotonic dystrophy associated CTG repeat in European and Japanese populations. Issue 11 (November 1992) - Davies, J; Yamagata, H; Shelbourne, P; Buxton, J; Ogihara, T; Nokelainen, P; Nakagawa, M; Williamson, R; Johnson, K; Miki, T
Abstract : Gene amplification using polymerase chain reaction (PCR) was carried out on DNA samples from a total of 92 normal subjects and 52 subjects with myotonic dystrophy (DM) from European and Japanese populations, to determine the copy number of the CTG repeat associated with DM for each group. In the two populations, the number of repeats on normal chromosomes only were compared, as CTG copy number on DM chromosomes was difficult to determine by PCR alone. In this study, normal chromosomes were found which had as many as 35 copies of the repeat, which is larger than the normal range reported previously but still does not overlap with the repeat number associated with DM pathology, which is at least 50 copies. Using data from normal chromosomes from unrelated subjects, the frequencies of five, 11, and 13 copies of the CTG repeat were found to be significantly different between the two populations, with five and 11 copies more commonly seen in the European population and 13 copies in the Japanese population. This difference may be the result of natural divergence of the normal chromosomes between the population groups.